The complete mitochondrial genome of Silurus asotus (Siluriformes: Siluridae: Silurus) and its phylogenetic analysis. Issue 2 (3rd July 2019) - Yang, Na; Li, Yingwen; Liu, Zhihao; Chen, Qiliang; Shen, Yanjun
Abstract: Silurus asotus is a widely distributed species, and mainly lives in the middle and lower layers of rivers, lakes, and reservoirs. In this study, we report the complete mitochondrial genome of S. asotus, which was 17, 385 bp in length, containing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region. Phylogenetic analyses indicated that S. asotus has a close relationship with S. soldatovi . This research work will provide some useful information on further molecular evolution studies of Siluridae species.